La lectura latinoamericana de Hannah Arendt en los escritos tempranos de Norbert Lechner (1970-1984) - Camou, Antonio; Di Pego, Anabella (2017)
La década que va del golpe militar en Chile (1973) a la recuperación democrática en Argentina (1983) dibuja simbólicamente un amplio territorio de nuevas visiones políticas entre los sectores "progresistas" latinoamericanos. Durante esos años la idea de "revolución" fue perdiendo terreno frente a una renovada estimación de las virtudes de la democracia como eje del campo político. Estas notas se concentran en analizar la inspiradora lectura de Hannah Arendt que Norbert Le-chner introduce en el debate latinoamericano sobre la democratización. Nuestra hipótesis señala que Lechner mantuvo un diálogo crítico permanente con el pensamiento alemán clásico y con-temporáneo. En particular, la apropiación, adaptación y recreación de la obra de Arendt fue fun-damental en tres planos. En el plano discursivo, Lechner recrea elementos de la visión arendtiana de la política que le permiten entenderla como una actividad humana intrínsecamente conflictiva y plural. En el plano político-institucional ambos autores desarrollan un registro reflexivo a medio camino entre la filosofía, las ciencias sociales y la literatura. Por último, en la dimensión socio-profesional, la figura arendtiana le ofrece a Lechner un modelo sugerente de intelectual autónomo por oposición al intelectual "orgánico", pero también al experto "neutral"
The decade that goes from the military coup in Chile (1973) to the democratic recovery in Argentina (1983) draws symbolically a broad territory of new political visions between the "progressive" sectors in Latin American. During those years the idea of "revolution" was losing ground facing a renewed estimate of the virtues of the democracy as axis of the political field. These notes concentrate on analyzing the suggestive reading of Hannah Arendt introduced by Norbert Lechner in Latin American debate on democratization. Our hypothesis says that Lechner maintained a critical permanent dialogue with the German classical and contemporary thought. In particular, the appropriation, adaptation and recreation of Arendt's work, was fundamental in three planes. At the discursive level, Lechner recreates elements of Arendt's vision of politics, allowing under- standing it as a human activity inherently conflictual and plural. At the institutional level, both authors develop a reflective record halfway between philosophy, social sciences and literature. Finally, at the socio-professional dimension, Lechner finds in Arendt's figure a promising model of autonomous intellectual, as opposed to the "organic" intellectual, and to the "neutral" expert. The decade that goes from the military coup in Chile (1973) to the democratic recovery in Argentina (1983) draws symbolically a broad territory of new political visions between the "progressive" sectors in Latin American. During those years the idea of "revolution" was losing ground facing a renewed estimate of the virtues of the democracy as axis of the political field. These notes concentrate on analyzing the suggestive reading of Hannah Arendt introduced by Norbert Lechner in Latin American debate on democratization. Our hypothesis says that Lechner maintained a critical permanent dialogue with the German classical and contemporary thought. In particular, the appropriation, adaptation and recreation of Arendt?s work, was fundamental in three planes. At the discursive level, Lechner recreates elements of Arendt's vision of politics, allowing under- standing it as a human activity inherently conflictual and plural. At the institutional level, both authors develop a reflective record halfway between philosophy, social sciences and literature. Finally, at the socio-professional dimension, Lechner finds in Arendt's figure a promising model of autonomous intellectual, as opposed to the "organic" intellectual, and to the "neutral" expert
Keywords: Lechner; Arendt; Democracia; Política; Pluralidad; Lechner; Arendt; Democracy; Politics; Plurality; Arendt, Hannah; Lechner, Norbert; América Latina; Argentina; Chile; Política; Democratización; Democracia; Filosofía contemporánea